OP0331 MAGNETIC RESONANCE IMAGING TENOSYNOVITIS AND OSTEITIS ARE INDEPENDENT PREDICTORS OF RADIOGRAPHIC AND MRI DAMAGE PROGRESSION IN RHEUMATOID ARTHRITIS PATIENTS IN CLINICAL REMISSION. (June 2019) - Møller-Bisgaard, Signe; Hørslev-Petersen, Kim; Ejbjerg, Bo; Hetland, Merete L.; Ørnbjerg, Lykke; Glinatsi, Daniel; Møller, Jakob Møllenbach; Boesen, Mikael; Stengaard-Pedersen, Kristian; Madsen, Ole; Jensen, Bente; Villadsen, Jan; et al.
Abstract : Background: Progression of structural joint damage occurs in 20-30 % of patients with rheumatoid arthritis (RA) in clinical remission 1 . Magnetic resonance imaging (MRI)-detected synovitis and in particular osteitis/bone marrow edema (BME) are known predictors of structural progression in both active RA and in remission, but the predictive value of adding MRI tenosynovitis assessment as potential predictor in patients in clinical remission has not been investigated. Objectives: To investigate the predictive value of baseline MRI inflammatory and damage parameters on 2 year MRI and X-ray damage progression in an RA cohort in clinical remission, following MRI and conventional treat-to-target (T2T) strategies. Methods: 200 RA patients in clinical remission (DAS28-CRP<3.2 and no swollen joints) on conventional DMARDs, included in the randomized IMAGINE-RA trial 2 (conventional DAS28 + MRI-guided T2T strategy targeting absence of BME vs conventional DAS28 guided T2T strategy) had baseline and 2 years contrast-enhanced MRIs of the dominant wrist and 2nd-5th MCP joints and X-rays of hands and feet performed, which were evaluated with known chronology by two experienced readers according to the OMERACT RAMRIS scoring system and Sharp/van der Heijde method, respectively. The following potentially predictive baseline variables: MRI BME, synovitis, tenosynovitis, MRI and X-ray erosion and joint space narrowing (JSN) score, CRP, DAS28, smoking status, gender, age and patient group were tested in univariate logistic regression analyses with 2-year progression in MRI combined damage score, Total Sharp Score (TSS), and MRI and X-ray JSN and erosion scores as dependent variables. Variables with p<0.1, age, gender and patient group were included in multivariable logistic regression analyses with backward selection. Results: Based on univariate analyses MRI BME, synovitis, tenosynovitis, x-ray erosion and JSN, gender and age were included in subsequent multivariable analyses. Independent MRI predictors of structural progression were BME (MRI progression) and tenosynovitis (MRI and X-ray progression), see table. MRI combined damage score: sum score of MRI erosion and JSN scores. Conclusion: This trial is the first to report that MRI tenosynovitis independently predicts both X-ray and MRI damage progression in RA patients in clinical remission. Further studies are needed to confirm MRI-determined tenosynovitis as predictor of progressive joint destruction in RA clinical remission. References: [1] Lillegraven, et al. Ann Rheum Dis 2012 [2] Møller-Bisgaard et al. JAMA, accepted Dec 2018 Acknowledgement: AbbVie for financial study support Disclosure of Interests: Signe Møller-Bisgaard Grant/research support from: Grants and non financial support from AbbVie during the conduct of the study, Speakers bureau: BMS, Kim Hørslev-Petersen Grant/research support from: AbbVie during the conduct of the study, Bo Ejbjerg: None declared, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen, Pfizer, Consultant for: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck, Samsung Bioepis, Lykke Ørnbjerg Grant/research support from: Unrestricted grant: Novartis, Daniel Glinatsi: None declared, Jakob Møllenbach Møller: None declared, Mikael Boesen Grant/research support from: Image Analysis Group, Eli Lilly, UCB, AbbVie, Esaote, Kristian Stengaard-Pedersen: None declared, Ole Madsen Grant/research support from: Sobi, AbbVie, Merck Sharp and Dohme, Pfizer, Eli Lilly, Celgene, Novartis, UCB, Sanofi Aventis, Roche, Amgen and BMS, Bente Jensen: None declared, Jan Villadsen: None declared, Ellen Margrethe Hauge Grant/research support from: Have received grants from Roche and Novartis, outside the submitted work., Speakers bureau: Have received personal fees from MSD, Pfizer, UCB and Sobi, Philip Bennett Grant/research support from: Eli Lilly, Merck Sharp and Dohme, Novartis, Oliver Hendricks Grant/research support from: AbbVie, Novartis, Karsten Asmussen: None declared, Marcin Kowalski: None declared, Hanne Merete Lindegaard: None declared, Henning Bliddal Grant/research support from: AbbVie. Oak Foundation, Niels Steen Krogh: None declared, Torkell Ellingsen: None declared, Agnete Nielsen: None declared, Lone Balding: None declared, Anne Grethe Jurik: None declared, Henrik Thomsen: None declared, Mikkel Ǿstergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB